"A monster that lives in our lives": experiences of caregivers of people with motor neuron disease and identifying avenues for support. Issue 4 (28th April 2016) - Anderson, Nicole Hennessy; Gluyas, Cathy; Mathers, Susan; Hudson, Peter; Ugalde, Anna
Abstract : Background: A developing body of evidence has provided valuable insight into the experiences of caregivers of people with motor neuron disease; however, understandings of how best to support caregivers remain limited. Aim: This study sought to understand concepts related to the motor neuron disease caregiver experience which could inform the development of supportive interventions. Design: A qualitative thematic analysis of a one-off semistructured interview with caregivers was undertaken. Setting/participants: Caregivers of people with motor neuron disease were recruited from a progressive neurological diseases clinic in Melbourne, Australia. Results: 15 caregivers participated. Three key themes were identified: (1) The Thief: the experience of loss and grief across varied facets of life; (2) The Labyrinth: finding ways to address ever changing challenges as the disease progressed; (3) Defying fate: being resilient and hopeful as caregivers tried to make the most of the time remaining. Conclusions: Caregivers are in need of more guidance and support to cope with experiences of loss and to adapt to changeable care giving duties associated with disease progression. Therapeutic interventions which target these experiences of loss and change are worth investigation. Trial registration number: ACTRN12615000120572, pre-results.